2020
DOI: 10.1186/s12903-020-01091-w
|View full text |Cite
|
Sign up to set email alerts
|

Adults’ dental treatment in 2001–2013 in Finnish public dental service

Abstract: Background All adults over 17 years of age have access to the Public Dental Service after the Finnish Dental Care Reform in 2001–2002. This study aimed to survey the treatment needs and treatment measures provided for adult patients and changes in these during the period 2001–2013. Methods Sing each person’s unique identifier, demographic data on dental visits during the period 2001–2013 were collected from municipal databases in five PDS-units covering 320,000 inhabitants. The numbers of visitors, those in n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In contrast, the (arbitrary) natural experiment with the application of regression discontinuity design minimizes confounding bias and thus makes compared populations exchangeable 29,30 ; the current study provides valuable knowledge about the population level effects of expanding oral health coverage on oral health outcomes in a general adult population otherwise nearly impossible to study in randomized experiments. Our findings about the effectiveness of more universal oral healthcare are likely still generalizable to today's Finland because, except from continuously decreased reimbursement level for private oral healthcare costs, 26 no major changes have occurred in oral healthcare provision provided for adults in Finland 50 . In addition, the authors do not expect that there have been dramatic improvements in effectiveness of oral healthcare services on oral health in Finland recent decades.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, the (arbitrary) natural experiment with the application of regression discontinuity design minimizes confounding bias and thus makes compared populations exchangeable 29,30 ; the current study provides valuable knowledge about the population level effects of expanding oral health coverage on oral health outcomes in a general adult population otherwise nearly impossible to study in randomized experiments. Our findings about the effectiveness of more universal oral healthcare are likely still generalizable to today's Finland because, except from continuously decreased reimbursement level for private oral healthcare costs, 26 no major changes have occurred in oral healthcare provision provided for adults in Finland 50 . In addition, the authors do not expect that there have been dramatic improvements in effectiveness of oral healthcare services on oral health in Finland recent decades.…”
Section: Discussionmentioning
confidence: 77%
“…Our findings about the effectiveness of more universal oral healthcare are likely still generalizable to today's Finland because, except from continuously decreased reimbursement level for private oral healthcare costs, 26 no major changes have occurred in oral healthcare provision provided for adults in Finland. 50 In addition, the authors do not expect that there have been dramatic improvements in effectiveness of oral healthcare services on oral health in Finland recent decades. For instance, wide adoption of risk-based recall intervals in Finland during last 30 years 51 may not have resulted in considerable improvements or deterioration of population oral health.…”
Section: Discussionmentioning
confidence: 96%
“…The exceptions are few. In Finland private practitioners represent just more than half of all dentists and provide approximately one half of all dental care ( 38 , 39 ). While there is some concern within the dental profession regarding how the growth in third-party payments will affect practices, most dental services across Europe continue to be funded by a mix of direct patient payment and government subsidy ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, in Finland almost two-thirds of the dentate adult population have at least one RCT tooth [24]. Of all the treatment provided in the PDS in Finland, approximately 5% was endodontic treatment in 2013 [25]. A recent study from southern Finland reported a success rate of 67% for RCTs performed by general dental practitioners [26].…”
Section: Introductionmentioning
confidence: 99%
“…were not evaluated. The explanatory variables for this study were age(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) years, 40-59 years, & ≥ 60 years), gender (male & female), RCT type (primary & secondary), number of dentists involved in treatment (1 clinician, 2 clinicians & ≥ 3 clinicians), education level of dentists involved (undergraduate dental student, general practitioner, specialized dentist), number of visits taken for RCT completion (1-2 visits, 3-4 visits & ≥ 5 visits), days from the first RCT visit until the root canal filling (0-14 days, 15-90 days & > 90 days), days from the first RCT visit until the final restoration of the tooth (0-30 days, 31-90 days & > 90 days), diagnosis to initiation of RCT (ICD 10 codes & written in patient register), instrumentation type (hand instrumentation & rotary instrumentation) and tooth types (incisors/canines, premolars & molars). If the tooth was re-treated by RCT within the follow-up time, it was registered.…”
mentioning
confidence: 99%